SAVING “JOGED MATARAM” VIA YOUTUBE: PRESERVATION AND DISSEMINATION OF LOCAL CULTURE IN THE DIGITAL AGE - Arif Eko Suprihono (Sanata Dharma University, 2022)
This research examines the paradigm shift of cultural policy within the Yogyakarta Royal Palace in embracing technology by means of social media to make the palace performance called “Joged Mataram” known to public. The data used in this qualitative research include various YouTube uploads of the screen-dance. Ethnographic method and detailed analysis of the uploads were put to use in this study. The results prove that the Yogyakarta Royal Palace had anticipated the digital age development by involving cultural citizens through the use of social media. Dance documentation products can be seen as cultural strategy in participating inthe digital life. It is also proven that the artistic approach of the Yogyakarta Royal Palace requires netizens’ participation to opine as to whether the palace performances can still meet the demands of the changing times.